1995
DOI: 10.1039/an9952000659
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of particulate-bound Cadmium of soils and its bioavailability

Abstract: A modified sequential chemical extraction procedure was developed for partitioning particulate Cd into eight fractions: exchangeable, carbonate-bound, metal-organic complex-bound, easily reducible metal oxide-bound, organic-bound, amorphous mineral colloid-bound, crystalline Fe oxide-bound, and residual. Results of experimental data on 16 surface soils of Saskatchewan, widely varying in physico-chemical properties, indicate the presence of little exchangeable Cd. Cadmium in these soils was predominantly in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0
6

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(73 citation statements)
references
References 19 publications
1
66
0
6
Order By: Relevance
“…The total Cd content and the Cd availability index (CAl) of the soils were determined following the microwave digestion technique (Krishnamurti et al, 1994) and the M NH 4 Cl extraction technique (Krishnamurti et al, 1995b ), respectively. The speciation of particulate-bound Cd of both the bulk and rhizosphere soils was carried out using the selective sequential extraction scheme of Krishnamurti et al ( 1995a). Cadmium in the digestion extracts of the soils was determined using a Perkin Elmer 2280 electrothermal atomic absorption spectrometer at 228.8 nm using a pyrolytically-coated tube and L'vov platform.…”
Section: Methodsmentioning
confidence: 99%
“…The total Cd content and the Cd availability index (CAl) of the soils were determined following the microwave digestion technique (Krishnamurti et al, 1994) and the M NH 4 Cl extraction technique (Krishnamurti et al, 1995b ), respectively. The speciation of particulate-bound Cd of both the bulk and rhizosphere soils was carried out using the selective sequential extraction scheme of Krishnamurti et al ( 1995a). Cadmium in the digestion extracts of the soils was determined using a Perkin Elmer 2280 electrothermal atomic absorption spectrometer at 228.8 nm using a pyrolytically-coated tube and L'vov platform.…”
Section: Methodsmentioning
confidence: 99%
“…Total concentrations of metals in soils are a poor indicator of metal toxicity since metals exist in different solid-phase forms that can vary greatly in terms of their bioavailability (Krishnamurti et al, 1995;Krishnamurti and Naidu;Huang and Gobran, 2005;Violante et al, 2010). Therefore the determination of total soil metal content alone is not a good measure of bioavailability and not a very useful tool to quantify contamination and potential environmental and human health risk (Violante et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Humic acids have a substantial capacity to complex metal ions, and the complexation process may affect the solubility of the metal ions (Zhang et al 1996). Studies on the speciation of particulate-bound Cd in temperate (Krishnamurti et al 1995) and tropical (Onyatta and Huang 1999) soils indicate that the metal-organic com- …”
mentioning
confidence: 99%
“…Humic acids have a substantial capacity to complex metal ions, and the complexation process may affect the solubility of the metal ions (Zhang et al 1996). Studies on the speciation of particulate-bound Cd in temperate (Krishnamurti et al 1995) and tropical (Onyatta and Huang 1999) soils indicate that the metal-organic com-plex-bound Cd is highly correlated with the bioavailability index of Cd. On the other hand, it was reported that adding HA to soils reduces the bioavailability of Cd (Taylor and Theng 1995;Shuman 1998); the nature of the soil's organic matter apparently influences this attribute.…”
mentioning
confidence: 99%